Analysis Of The Effect Of Islamic Product Attributes, Servicescape, And Interpersonal Communications On Customer Satisfaction Bank BTN Syariah KCPS Ngaliyan - Nurudin Nurudin; Khoirul Anwar; Hidayaturrosyida Hidayaturrosyida (AL-ARBAH: Journal of Islamic Finance and Banking, 2020)
Purpose - This study aims to determine the effect of Islamic product attributes, service scape, interpersonal communication on customer satisfaction at Bank BTN Syariah KCPS Ngaliyan.Method - The method used in this research is quantitative method, where this method is carried out by distributing questionnaires to BTN Syariah KCPS Ngaliyan customers. Samples were taken as many as 100 respondents with incidental sampling technique.Result - The results show that the variable attributes of Islamic products, servicescape, and interpersonal communication have a positive and significant effect on customer satisfaction of BTN Syariah KCPS Ngaliyan.Implication - This research can be used for references related to matters that affect customer satisfaction.Originality- This study analyzes the variable attributes of Islamic products, servicescape, and interpersonal communication on customer satisfaction.